Efeito imunomodulador de leveduras frescas em novilhas confinadas - Virmond, Maurício Paulo (2019)
Considering that a more energetic diet may lead to subacute ruminal acidosis in cattle, the use of Saccharomyces cerevisiae-based additives is believed to minimize the severity of this disease, attenuating its effects on bovine immunity and, consequently, the occurrence of respiratory diseases. For this purpose, 32 heifers of Angus blood were used, with average initial weight of 350 kg and mean age of 11 months, fed on 50% corn silage and 50% concentrate distributed randomly in two control groups (7g / animal / cornbread day) and yeast group (7 g / animal / day of the commercial product containing fresh yeasts). In four moments, leukogram, serum haptoglobin, measured by the ELISA technique was performed; oxidative metabolism of neutrophils by the nitro blue tetrazolium technique and occurrence of respiratory disease by nostril temperature and nasal secretion score. At 105 days, the animals were slaughtered and pulmonary fragments of the ventral cranial lobe were harvested for histopathological evaluation. The animals in the control group showed increased leukocytes, neutrophils and serum haptoglobin, as well as greater clinical signs of respiratory diseases and higher histopathological pneumonia scores. On the other hand, the animals in the yeast group showed lower leukocyte and neutrophil counts, increased neutrophil oxidative metabolism and decreased serum haptoglobin, as well as lower nasal secretion, lower respiratory rate and lower pneumonia scores, allowing the conclusion that live yeasts attenuated the elects of confinement on the innate immune system, resulting in higher animal health.